THE ROLE OF DEPARTEMENT BINA MARGA OF RIAU PROVINCE IN THE MAINTENENCE STREET AND BRIDGE IN SIAK REGENCY 2017 - Uci Resty Pratama; Wan Asrida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Street and bridge are the main transportation access to support the society in doing daily activity. The street and bridge construction could be done in all areas, thereby the infrastructure  contstruction especially in Siak Regency could be balanced. Riau Province infrastructure construction has not optimal yet for the province’s street and bridge in Siak regency because there found worse in 2017.  That is why the function of Dinas Bina Marga of Riau Province is important to collaborate optimaly in their job description and function for keeping the street and the bridge in Siak regency, in order to increase economy development in Riau province.Hopefully, this research could be able to evaluate the duty of Dinas Bina Marga of Riau province in looking after the street and the bridge in Siak Regency. In doing this research, researcher used qualitative research method. Primary and secondary data are used in this research. Besides, researcher used interview and documentation for the data collection. The result is the function of Dinas Bina Marga has not optimal yet in taking care the street and the bridge, for the proof of it, the two programmes which are the rehabilitation for the street and the bridge also the inspection of the street are not well done yet. There are only two of six programmes has be done from rehabilitation, on the other side for the inspection that is only one a year finished in all of Riau provice area.  Keywords : the function of Dinas Bina Marga, Taking care of Street and bridge, street and bridge rehabilitation and inspection.